2013
DOI: 10.1093/humrep/det251
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the outcome of frozen-thawed embryo transfer

Abstract: The presence of ≥1 top quality embryo at any step of the freezing and thawing process increases the chance of pregnancy. The data do not support the freezing of all embryos for transfer in order to improve the outcome. A top quality embryo transferred in FET may even have the same potential as in a fresh cycle. On the contrary, LBR in the group with no top quality embryos frozen was quite low (10.4%), raising the question of whether a re-evaluation of freezing criteria is necessary to avoid costly treatments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
80
3
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 21 publications
10
80
3
3
Order By: Relevance
“…Women undergoing frozen transfer cycles, specifically, are unable to provide adequate endogenous P4 and require progesterone supplementation to initiate and maintain the secretory endometrium and pregnancy. There has been previous research into luteal phase support in frozen cycles, which has demonstrated that supplementation of progesterone does impact outcome in FET [2]. Several studies have shown that there is an increase in live birth rate with P4 luteal support but there is mixed data on whether P4 support lowers the miscarriage or biochemical pregnancy rate [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Women undergoing frozen transfer cycles, specifically, are unable to provide adequate endogenous P4 and require progesterone supplementation to initiate and maintain the secretory endometrium and pregnancy. There has been previous research into luteal phase support in frozen cycles, which has demonstrated that supplementation of progesterone does impact outcome in FET [2]. Several studies have shown that there is an increase in live birth rate with P4 luteal support but there is mixed data on whether P4 support lowers the miscarriage or biochemical pregnancy rate [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The cryopreservation is known to damage some of the embryo's cells [49], leading to a conclusion that this is a mechanism for a positive selection of Bmore aggressive^blastocysts. According to Veleva et al [50], the processes of freezing and thawing cause damage to the embryos, but the extent of the damage depends on the embryo's quality. Top quality embryos are more viable than embryos of a poorer quality, and the transfer of a frozenthawed top quality embryo may lead to better results.…”
Section: Discussionmentioning
confidence: 99%
“…Luteal phase support was given in five studies [36,[40][41][42][43]; the ORs for clinical pregnancy and live birth rates were not significantly different (OR 1.32 (95 % CI 0.90-1.93; four studies) and 1.47 (95 % CI 0.72-3.03; two studies), respectively).…”
Section: Tnc Versus Ac Without Suppressionmentioning
confidence: 92%
“…A total of eight studies, all being retrospective cohort studies [35,36,[38][39][40][41][42][43], making a total of 8762 ET cycles, were included.…”
Section: Tnc Versus Ac Without Suppressionmentioning
confidence: 99%